Islamic Education Management Strategies in Increasing Students' Active Participation in the Classroom: A Special Approach Perspective: Strategi Manajemen Pendidikan Islam dalam Meningkatkan Partisipasi Aktif Siswa di Kelas: Perspektif Pendekatan Khusus - Akmal; Ilham; Mukmin (Mapendis: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the role of Islamic educational management strategies in increasing active student participation in the classroom through a specific approach. This study used library research methods by reviewing scientific literature published in the last five years, drawn from various academic databases and selected based on specific inclusion criteria. Data analysis was conducted using a thematic content analysis approach to identify patterns, conceptual relationships, and key findings regarding the effectiveness of Islamic educational management strategies. The results of the study indicate that specific approaches such as the application of discussion methods, demonstrations, role-playing, and contextual learning can increase students' interest in learning, their courage in discussions, and their ability to reflect on the material. Furthermore, the integration of digital media in learning, when supported by teachers' managerial competence in managing interactive classes, has also been shown to strengthen student participation. Conversely, conventional and one-way learning approaches tend to reduce student engagement due to limited space for expression and interaction. This study concludes that Islamic educational management strategies based on a specific approach are highly relevant to the demands of modern learning and effective in increasing active student participation. Further research is recommended to be conducted empirically through experiments or the application of digital media to measure the direct impact on learning outcomes and student engagement.